Excess Readmission rates for Heart Failure and Pneumonia by Hospital Type - Viraj Brahmbhatt (Ital Publication, 2022)
The improvement of quality care is a major goal for modern healthcare. Quality of care is often measured through readmission rates for specific conditions such as heart failure, pneumonia, total arthroplasty of the knee/hip, etc. This data has been used by the Center for Medicare and Medicaid Services (CMS) to adjust reimbursement rates for hospitals with excessive readmissions. Different hospital operations and management models possess structural differences that may impact the rates of readmission. This study investigated whether there were significant differences in the readmission rates for academic, non-profit, and for-profit hospitals. The results may be important in reshaping guidelines to assess hospitals based on readmission rates. The average excess readmissions for heart failure were in non-profit hospitals for 1.0047, for-profit hospitals for 1.013, and academic hospitals for 0.975. The ANOVA for this set returned a p-value of 1.70284E-05, meaning that the results were statistically significant. As such, academic hospitals have statistically lower readmission rates for heart failure. The excess readmission rates for pneumonia yielded 1.025 for non-profit, 1.024 for for-profit, and 0.99 for academic hospitals. The ANOVA returned a p-value of 2.4899E-09, which suggests the differences seen are statistically significant. As such, academic hospitals also have a statistically lower rate of pneumonia readmissions. The study has implications for consumer decision-making when choosing a hospital. In addition to this, algorithms for benchmarking as well as CMS adjustments to reimbursement rates may consider factoring in the hospital ownership type.   Doi: 10.28991/SciMedJ-2022-04-02-03 Full Text: PDF